Four essays on the urban labour market in India - Bhalotra, S; Bhakotra, Sonia Radhika (1996)
﻿ This thesis explores labour market processes in urban India. Investigating large and persistent differentials in urban unemployment rates across the Indian states, we find that regions with higher wage push or better amenities have higher unemployment rates, controlling for labour force composition. The differentials are maintained by rural-urban migration rather than by barriers to inter-state migration. Our investigation of wage determination yields evidence of imperfect competition in the labour market which is not simply 'institutional'. Indian firms pay efficiency wages which induce sufficient productivity gains to pay for themselves. After identifying the long and short run structural processes in the labour market, we consider recent aggregate trends in India's factory sector. There was negative employment growth in the 1980s even as output growth touched record levels. Our analysis suggests that this had less to do with wage growth, as proposed by the World Bank, and more to do with increasing work intensity, encouraged by wage incentives, improved infrastructure and increased competition. Considerable slack was inherited from the past, evidence of which flows from the wage and production function estimates. We find that increased labour utilization raises capacity utilization. This is important because Indian industry has chronically carried large excess capacity. A breakthrough in total factor productivity growth accompanied declining employment in the 1980s and has been interpreted as the reward of deregulation in this decade. Existing studies mismeasure productivity growth by neglecting labour utilization (hours) and assuming perfectly competitive product markets. We produce new estimates at the aggregate and industry levels. A natural ceiling to hours worked moderates bad news on the employment front and good news on the productivity front. Our analyses are expected to contribute to the evaluation of current and controversial policy changes in India.